2021
DOI: 10.1088/1757-899x/1024/1/012112
|View full text |Cite
|
Sign up to set email alerts
|

HERA Mission LIDAR Altimeter Implementation

Abstract: The Asteroid Impact & Deflection Assessment (AIDA) is a collaboration between the NASA DART mission and ESA Hera mission. The aim scope is to study the asteroid deflection through a kinetic collision. DART spacecraft will collide with Didymos-B, while ground stations monitor the orbit change. HERA spacecraft will study the post-impact scenario. The HERA spacecraft is composed by a main spacecraft and two small CubeSats. HERA will monitor the asteroid through cameras, Radar, Satellite-to-Satellite doppler t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 0 publications
0
12
0
Order By: Relevance
“…The emitter has a microchip laser that emits pulses of light at 1535 nm, with a pulse energy of 100 μJ and a pulse width of 2 ns. The radiometric model of this instrument was discussed in [8,9], where the link equation is used to calculate the received pulse energy, which depends on the transmitted laser pulse energy, the emitter and receiver transmittance, the asteroid reflectance, the geometry of the receiver telescope, the distance between LIDAR and the target and the overlap between the emitter and receiver. This equation is important to calculate the critical parameters required for the LIDAR receiver aperture.…”
Section: Figure 1 Lidar Receiver Telescope Optical Design (Zemax)mentioning
confidence: 99%
See 1 more Smart Citation
“…The emitter has a microchip laser that emits pulses of light at 1535 nm, with a pulse energy of 100 μJ and a pulse width of 2 ns. The radiometric model of this instrument was discussed in [8,9], where the link equation is used to calculate the received pulse energy, which depends on the transmitted laser pulse energy, the emitter and receiver transmittance, the asteroid reflectance, the geometry of the receiver telescope, the distance between LIDAR and the target and the overlap between the emitter and receiver. This equation is important to calculate the critical parameters required for the LIDAR receiver aperture.…”
Section: Figure 1 Lidar Receiver Telescope Optical Design (Zemax)mentioning
confidence: 99%
“…The HERA LIDAR is a compact instrument with an overall mass of less than 2 kg. The engineering model of the LIDAR, called HELENA, was addressed in [8,9]. The lessons learned from HELENA demonstrated that it is helpful to optimize the thermal and mechanical design of the LIDAR flight model (PALT).…”
Section: Thermo-mechanical Designmentioning
confidence: 99%
“…The Planetary ALTimeter (PALT) mechanical design has been optimized on different aspects to meet the requirements established for the HERA mission. In [6][7][8], the HELENA LIDAR's performance was evaluated regarding weaker requirement of shock, static simulation of 5G in two different directions, and thermal conductive simulations between −40 C. The main objective was to study the secondary mirror deformation towards the base of the telescope, and maximum stresses. Two different materials (aluminum and titanium) were assessed for the upper part of the LIDAR telescope.…”
Section: Previous Researchmentioning
confidence: 99%
“…The design was iterated several times, with the focus being on the initial design and a final design. The first design of the isostatic bipod mounts was presented in HELENA [6,7], which was the starting point of the isostatic bipod mount for PALT. This first design is depicted in Figure 2.…”
Section: Designmentioning
confidence: 99%
See 1 more Smart Citation